2023
DOI: 10.1002/tox.23952
|View full text |Cite
|
Sign up to set email alerts
|

REG3A promotes proliferation and DDP resistance of ovarian cancer cells by activating the PI3K/Akt signaling pathway

Lingling Jiang,
Yinglei Liu,
Manhua Liu
et al.

Abstract: This study explored the effect of Regenerating Islet‐Derived 3‐Alpha (REG3A) on ovarian cancer (OC) progression. REG3A expression was scrutinized in clinical tissues of 97 OC cases by quantitative real‐time polymerase chain reaction (qRT‐PCR). REG3A expression in OC cells and cisplatin (DDP) resistance OC cells was regulated by transfection. LY294002 (10 μM, inhibitor of the PI3K/Akt signaling pathway) was used to treat OC cells and DDP resistance OC cells. Cell counting kit‐8 and methyl‐thiazolyl‐tetrazolium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Ye et al reported a positive correlation between REG3A overexpression and increased Akt phosphorylation in colorectal cancer cells [ 15 ]. A recent study by Jiang and colleagues reported that REG3A enhanced the proliferation of ovarian cancer cells through activating PI3K/Akt signaling pathway [ 47 ]. Additionally, REG3A is involved in the activation of the Akt cascade in glioma cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ye et al reported a positive correlation between REG3A overexpression and increased Akt phosphorylation in colorectal cancer cells [ 15 ]. A recent study by Jiang and colleagues reported that REG3A enhanced the proliferation of ovarian cancer cells through activating PI3K/Akt signaling pathway [ 47 ]. Additionally, REG3A is involved in the activation of the Akt cascade in glioma cells [ 48 ].…”
Section: Discussionmentioning
confidence: 99%